2017
DOI: 10.1039/c7fo00539c
|View full text |Cite
|
Sign up to set email alerts
|

Human milk peptides differentiate between the preterm and term infant and across varying lactational stages

Abstract: Variations in endogenous peptide profiles, functionality, and the enzymes responsible for the formation of these peptides in human milk are understudied. Additionally, there is a lack of knowledge regarding peptides in donor human milk, which is used to feed preterm infants when mother's own milk is not (sufficiently) available. To assess this, 29 human milk samples from the Dutch Human Milk Bank were analyzed as three groups, preterm late lactation stage (LS) (n = 12), term early (n = 8) and term late LS (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…Effective preventive and therapeutic strategies are desperately needed for this devastating condition. Evidence from epidemiological studies has shown that breast milk feeding for the preterm neonate is beneficial in reducing morbidity of NEC . One of the leading potential mechanisms could be related to the rich source of exosomes in breast milk .…”
Section: Discussionmentioning
confidence: 99%
“…Effective preventive and therapeutic strategies are desperately needed for this devastating condition. Evidence from epidemiological studies has shown that breast milk feeding for the preterm neonate is beneficial in reducing morbidity of NEC . One of the leading potential mechanisms could be related to the rich source of exosomes in breast milk .…”
Section: Discussionmentioning
confidence: 99%
“…In blood, the stability is highly dependent on the spectrum of active proteases and protease inhibitors highly correlated to the activation level of the coagulation and complement system [34]. The protease activity in breast milk seems to be less variable but varies depending on the lactation period and the gestational age [35]. A search of peptide and truncated peptide sequences against the milk protein peptide database revealed 239 bioactive molecules, all originating from CSN2 and CSN1S1.…”
Section: Discussionmentioning
confidence: 99%
“…2 Bioactive peptides have the potential to play a prominent role in human health by affecting the digestive system, endocrine functions, cardiovascular risk, immune response and nervous systems, 3 and infant growth and development through several lactational stages. 4 Publicly accessible databases such as Biopep, 5 StraPep, 6 STAPdb, 7 PepBank 8 and others continuously update the knowledge on biologically active food peptides with physiological significance beyond their pure nutritional value.…”
Section: Introductionmentioning
confidence: 99%